Analyzing rainfall effects on agricultural income: Why timing matters - Marcelo Torres; Richard E. Howitt; Lineu Neiva Rodrigues (EconomiA, 2019)
Water is a key input to agricultural production and therefore fluctuations in water availability may impact agricultural productivity and revenue. Climate science tells us that most of these fluctuations are increasingly resulting from intra-year, instead of interyearly, shifts in the timing and intensity of rainfall. Consequently predictions of the economic effects of these fluctuations would likely differ depending on how these shifts are taken into account by the empirical models. To investigate this, the present paper introduces a novel hydro-economic model in which the timing and intensity of rainfall affect the productivity of a partially irrigated agricultural system in Brazil. The specification of the production function is designed to reflect intra-year, in a monthly or seasonal basis, and interyearly shifts on rainfall to show how the opportunity cost of supplementary irrigation supply varies with changes in the timing and intensity of rainfall. Results suggest that the timing of rainfall is indeed an important economic variable and models that take into account shifts only on a yearly basis will tend to underestimate the impacts of water scarcity on agricultural income.
Keywords: Q10; Q25; Q54; 330; Agricultural income; Applied microeconomics; Hydroeconomic modeling; Positive mathematical programming; Temporal resolution; Water resources